2010
DOI: 10.1016/j.neuroimage.2009.12.108
|View full text |Cite
|
Sign up to set email alerts
|

A group independent component analysis of covert verb generation in children: A functional magnetic resonance imaging study

Abstract: Semantic language skills are an integral part of early childhood language development. The semantic association between verbs and nouns constitutes an important building block for the construction of sentences. In this large-scale functional magnetic resonance imaging (fMRI) study, involving 336 subjects between the ages of 5 and 18 years, we investigated the neural correlates of covert verb generation in children. Using group Independent Component Analysis (ICA), seven task-related components were identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
101
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(116 citation statements)
references
References 164 publications
(246 reference statements)
15
101
0
Order By: Relevance
“…9,33 ICA was previously used in fMRI studies of language to map transient randomly occurring neuropsychological events without an a priori knowledge of the paradigm. 34,35 Our ICA-GLM approach called for selecting the IC that presented the largest temporal correlation coefficient with the language task predictor and which, consistent with a recent study, 36 usually revealed the contemporary activation of the left IFG and TPJ (Table). The fact that a single IC visualized both the anterior and posterior regions for speech is also consistent with studies on resting-state functional-connectivity MR imaging, which reported that these regions were functionally connected.…”
Section: 27supporting
confidence: 75%
“…9,33 ICA was previously used in fMRI studies of language to map transient randomly occurring neuropsychological events without an a priori knowledge of the paradigm. 34,35 Our ICA-GLM approach called for selecting the IC that presented the largest temporal correlation coefficient with the language task predictor and which, consistent with a recent study, 36 usually revealed the contemporary activation of the left IFG and TPJ (Table). The fact that a single IC visualized both the anterior and posterior regions for speech is also consistent with studies on resting-state functional-connectivity MR imaging, which reported that these regions were functionally connected.…”
Section: 27supporting
confidence: 75%
“…2006; Karunanayaka et al. 2010). Finally, a voxel‐wise random effects analysis (one‐sample t ‐test) is performed on individual IC maps to determine the group IC maps.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the model-free nature of ICA allows for the prospect that signal associated with different aspects of processing may diverge from an omnibus model of the hemodynamic response. Because these features of ICA tend to increase statistical power, ICA is often a more sensitive technique than the computationally-simpler GLM approach, and consequently typically reveals more regions of statistically significant activation (e.g., Karunanayaka, Schmithorst, Vannest, Szaflarski, Plante, & Holland, 2010; Schmithorst, Holland, & Plante, 2006; 2007). …”
Section: Introductionmentioning
confidence: 99%